Plasma Science and Technology Progress in Physical States and Chemical Reactions - Mieno, Tetsu (IntechOpen, 2016)
In the early twentieth century, Dr. Irving Langmuir actively studied plasma discharge and surface science. Since then, great progress has been made in the development of applications of discharges and plasmas such as discharge lamps, electric tubes, and arc welding. In relation to studies on space physics and controlled nuclear fusion, plasma physics has greatly advanced. Plasma chemistry has also progressed along with its applications in LSI fabrication technology, the chemical vapor deposition of functional films, and the production of nanomaterials. In the twenty-first century, the further development of applications of plasma physics and plasma chemistry is certainly expected. In this book, 18 chapters on the recent progress in plasma science and technology have been written by active specialists worldwide.